The Healthcare System and the Hidden Traps of its Logistics - MIHOREANU, Larisa; COSTEA, Carmen; STEFANESCU, Alexandru (Journal of Economic Development, Environment and People, 2016)
The analysis of the society development is more complex than one might think at first glance. So is the market. There are sides and activities not easy to see and one needs high capabilities and strength to look beyond the appearances and see what’s not visible. The most dangerous games happen inside the crossing boarder sectors that no men land between legal and black activities; that is a very vivid area where actions and profits are higher than ever can imagine. This side of the economy has its tentacles piercing the legal boarder of the sound economy and functions through movements that effect all sectors and activities pushing to get huge black profits. Romanian health sector makes no exception. The wish to get getting higher and higher profits doesn’t go with performing and satisfactory management when the corporate liaisons are oriented more on discussions and less on integrative quality and satisfaction of people concerned; thus the so called guys in white coats are necessarily oriented to another sort of motivation – linked to networked process of getting black money and laundering it through the backing support of the informal more than legal procedures. The loss is always paid by individuals and community as: fewer funds from taxes, stratified salaries caused subjective application of norms and procedures, decreased labour quality, inappropriate economic behaviour, losses in the robustness of the future generations. Through such channels, the informal economy last running building up a strong logistic that develops parallel activities, utterly designed to respect specific customs based on gestural understanding and communication that encourage the unfairness, the aggressiveness in competition and hot money/short run investments. This paper intends to catch some of the general aspects of what black and informal economy can carry out, through procedures that use the imperfect legal methodology decision and its implementation into informal possibility to fraud both the public funds and peoples savings. The paper touches also the public consequences of the undeclared work of employees of public and private sectors emphasising also the need to identifying some specific roles to play in the future by the services business planning, the law application and the policy of autonomy to help the medical market blossom vigorously. In conclusion, we sustain that the fair action is not an alternative conception of developing, in the fashion, neither of human evolution nor of need-based growth. There is a higher need to model individual awareness and motivation in the direction of increasing the self-responsibility for building a better environment based on a proactive personal development, from within and connected to the outer world.